INDIVIDUAL TYPES OF CORPORATE RISKS: INDUSTRY DISTRIBUTION IN THE CASE OF SLOVENIA - Jagrič, Timotej; Amon, Aleksandra; Jagrič, Vita; Zdolšek, Daniel; Taškar Beloglavec, Sabina (Economic Outlook, 2023)
The contribution deals with individual risks in the Slovenian business environment. We encompassed eighteen different corporate risks in our research. The companies were asked to assess their exposure to the individual risk type in 2023. They have chosen their exposure rate from very little to significant on a Likert four-point scale. The results presented are based on answers from 120 large and middle-sized companies and are analysed according to their economic activity. We explored the research question of whether exposure to a particular type of risk differs among industries. This risk assessment is part of a broader annual Slovenian Corporate Risk Monitor 2023 project.